2015
DOI: 10.3109/02703181.2015.1009227
|View full text |Cite
|
Sign up to set email alerts
|

Older Peoples’ Perceived Benefits of Feldenkrais Method Classes

Abstract: Aims: The Feldenkrais Method of movement education has gradually gained in popularity in recent years; however, there is little research explaining why people engage in the Feldenkrais Method. The aim of this study was to understand the benefits perceived by older people from participation in an "awareness through movement" (ATM) class, as described in the Feldenkrais Method of movement education. This study aimed to be a foundation for future quantitative research and guide the selection of appropriate outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This orientation is the very countering of the mind's tendency to wander, since it compels our attention to remain grounded in present bodily sensations. A qualitative study (Broome et al, 2015) of elders participating in Feldenkrais lessons found that they self-reported enhanced mindfulness as one of its benefits. We argue that Feldenkrais has the potential to enhance mindfulness in ways that help people remain in the present, enhancing their capacities for empathic leadership.…”
Section: Mindfulnessmentioning
confidence: 99%
“…This orientation is the very countering of the mind's tendency to wander, since it compels our attention to remain grounded in present bodily sensations. A qualitative study (Broome et al, 2015) of elders participating in Feldenkrais lessons found that they self-reported enhanced mindfulness as one of its benefits. We argue that Feldenkrais has the potential to enhance mindfulness in ways that help people remain in the present, enhancing their capacities for empathic leadership.…”
Section: Mindfulnessmentioning
confidence: 99%
“…The concept was developed and created by Moshe Feldenkrais (1904Feldenkrais ( -1984 as a method of self-development and a new approach to the body during a rehabilitation period after a knee injury while practising judo (Eddy, 2009). The Feldenkrais Method has been developed in mindfulness work (Mattes, 2016;Wallman-Jones et al, (2023) or the level of psychological well-being (Wallman-Jones et al, 2023) in older people (Broome et al, 2015).…”
Section: Feldenkrais Methodsmentioning
confidence: 99%
“…As noted, the research on the FM among singers is limited; however, there have been a number of peer-reviewed studies in the medical and rehabilitation literature that have linked Feldenkrais participation to improved health and wellness, reported as physical and psychological benefits (Broome et al, 2015). Some researchers cautioned that results must be considered carefully as many of these studies have design limitations that mitigate their reported positive results (Buchanan, 2012; Buchanan & Ulrich, 2001; Stephens, 2004).…”
Section: The Feldenkrais Method1 Of Somatic Educationmentioning
confidence: 99%